Clinical Characteristics of Subependymal Giant Cell Astrocytoma in Tuberous Sclerosis Complex - Jansen, Anna C.; Belousova, Elena; Benedik, Mirjana P.; Carter, Tom; Cottin, Vincent; Curatolo, Paolo; Dahlin, Maria; D'Amato, Lisa; d'Augères, Guillaume Beaure; de Vries, Petrus J.; Ferreira, José C.; Feucht, Martha; et al. (Frontiers in Neurology, 2019)
Background: This study evaluated the characteristics of subependymal giant cell astrocytoma (SEGA) in patients with tuberous sclerosis complex (TSC) entered into the TuberOus SClerosis registry to increase disease Awareness (TOSCA). Methods: The study was conducted at 170 sites across 31 countries. Data from patients of any age with a documented clinical visit for TSC in the 12 months preceding enrolment or those newly diagnosed with TSC were entered. Results: SEGA were reported in 554 of 2216 patients (25%). Median age at diagnosis of SEGA was 8 years (range, 0-51), with 18.1% diagnosed after age 18 years. SEGA growth occurred in 22.7% of patients aged ≤ 18 years and in 11.6% of patients aged > 18 years. SEGA were symptomatic in 42.1% of patients. Symptoms included increased seizure frequency (15.8%), behavioural disturbance (11.9%), and regression/loss of cognitive skills (9.9%), in addition to those typically associated with increased intracranial pressure. SEGA were significantly more frequent in patients with TSC2 compared to TSC1 variants (33.7% vs 13.2 %, p<0.0001). Main treatment modalities included surgery (59.6%) and mammalian target of rapamycin inhibitors (49%). Conclusions: Although SEGA diagnosis and growth typically occurs during childhood, SEGA can occur and grow in both infants and adults.